2014
DOI: 10.1098/rspb.2014.1291
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of large density changes on relative testes size in fluctuating populations of sympatric vole species

Abstract: Across species, there is usually a positive relationship between sperm competition level and male reproductive effort on ejaculates, typically measured using relative testes size (RTS). Within populations, demographic and ecological processes may drastically alter the level of sperm competition and thus, potentially affect the evolution of testes size. Here, we use longitudinal records (across 38 years) from wild sympatric Fennoscandian populations of five species of voles to investigate whether RTS responds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Sexually selected strategies are adjusted by ecological factors such as food restriction (Janicke, David & Chapuis, ), and RTS or ejaculate expenditure can be readily altered by food resources available to males (e.g. the dung fly Scatophaga (= Scathophaga ) stercoraria Simmons & Parker, ; the moth Plodia interpunctella , Gage, ; the tick Amblyomma cajennense , Anholeto et al ., ; voles, Klemme, Soulsbury & Henttonen, ; the moth Achroia grisella , Cordes et al ., ). The fact that GSI changes often quite radically through the year in many seasonal breeding invertebrates and vertebrates, and is so much used by biologists to determine peak breeding season, also implies a trade‐off between soma and gonads.…”
Section: Trade‐offsmentioning
confidence: 97%
“…Sexually selected strategies are adjusted by ecological factors such as food restriction (Janicke, David & Chapuis, ), and RTS or ejaculate expenditure can be readily altered by food resources available to males (e.g. the dung fly Scatophaga (= Scathophaga ) stercoraria Simmons & Parker, ; the moth Plodia interpunctella , Gage, ; the tick Amblyomma cajennense , Anholeto et al ., ; voles, Klemme, Soulsbury & Henttonen, ; the moth Achroia grisella , Cordes et al ., ). The fact that GSI changes often quite radically through the year in many seasonal breeding invertebrates and vertebrates, and is so much used by biologists to determine peak breeding season, also implies a trade‐off between soma and gonads.…”
Section: Trade‐offsmentioning
confidence: 97%
“…Males reared in the presence of [more] rivals or their cues have been shown to develop larger testes (Gage, ; Stockley & Seale, ; Scharer & Ladurner, ; Tan et al ., ; Bailey et al ., ), a faster rate of spermatogenesis (Giannakara et al ., ), larger (Bailey et al ., ; Bretman et al ., ) or smaller (Sloan et al ., ) accessory glands, and better body condition (Bailey et al ., ; Simmons & Buzatto, ). In vertebrates, correlational evidence from natural populations has suggested that males may adjust their expenditure on sperm production according to environmental or social cues that are indicative of reproductive competition (Brown & Brown, ; Long & Montgomerie, ; Firman & Simmons, ; Dziminski et al ., ; Klemme et al ., ), whereas empirical studies that have manipulated the social environment to emulate different levels of reproductive competition during sexual development have produced mixed results (Evans & Magurran, ; Ramm & Stockley, ; Lemaitre et al ., ; Smith & Ryan, ; Firman et al ., ; Ramm et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Other traits involved in mate searching that may also be favoured at low population densities include larger wings, more flight muscle and larger visual sensory organs [10,13,15]. Investment in these traits may be traded-off against other reproductive functions: for example, the risk of sperm competition may increase with population density, and males may respond with greater investment in sperm production [9,11,15,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%